Pengaruh Live Streaming dan Flash Sale terhadap Impulse Buying Skincare di TikTok Shop bagi Masyarakat Kecamatan Karang Bahagia - Sri Winda Hardiyanti Damanik; Adi Suprayoga; Fatimah Az-Zahra (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This study aims to examine the influence of live streaming and flash sales on impulse buying behavior on TikTok Shop, specifically in the context of skincare product purchases. A quantitative approach with an associative research type was employed. Data were collected through a questionnaire distributed to residents of Karang Bahagia District who met specific criteria. The sampling technique used was purposive sampling, with a total of 96 respondents. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests including normality, linearity, heteroscedasticity, and multicollinearity tests. Data processing was performed using SPSS version 26. The results revealed that simultaneously, both independent variables live streaming and flash sales have a significant effect on impulse buying (F-value = 18.909 > F-table = 3.09; sig. = 0.000 < 0.05). Theregression equation obtained is Y = 40.517 + 0.286X₁ + 0.080X₂. The coefficient of determination (R²) is 0.290, indicating that 29.0% of the variation in impulse buying is explained by live streaming and flash sale variables, while the remaining 71.0% is influenced by other factors not examined in this study.